Early arthritis in children – first results of prospective follow up - S. O. Salugina; N. N. Kuzmina; G. R. Movsisyan; E. S. Fedorov; S. V. Arsenjeva; E. N. Alexandrova; A. A. Novikov; A. A. Baranov (Научно-практическая ревматология)
Objective. To perform a prospective investigation of clinico-laboratory and sonographic picture of juvenile arthritis (JA) onset, to follow up its evolution during the first years of the disease, to prove the program of appropriate treatment.Material and methods. 128 pts with early JA (61% girls and 39% boys aged 1,5 to 16 years) were included. Disease duration varied from 2 weeks to 6 months. General health, joint status, disease activity, functional class (Steinbroker), systemic and organ disturbances, laboratory activity indices, immunologic parameters (ANF, RF) were assessed. Antibodies to cyclic citrullinated peptide (ACCP) were evaluated in 38 pts by immunofluorescence method (IFM) with commercial kits “Axis Shild Diagnostics Limited, UK”, antibodies to modified citrullinated vimentin (MCV) were assessed in 60 pts by IFM with commercial kits “Orgentec” (Germany). Pts were examined every 3 months, the main investigations were repeated after 6, 12 and 24 months. Accuracy of the diagnosis was checked at every examination.Results. Mono- oligoarticular variant of onset was found in 68,6% polyarticular – in 21,4%, systemic – in 10% of pts. Knee and ankle joints were involved first (61% and 24% respectively), later – wrist (13%) and hand joints (17%). Morning stiffness was absent in 85% of pts. 37% of pts had ANF and 13,2% - RF. 10,5% were ACCP positive and 28,3% – MCV positive. Antibodies correlated with polyarticular variant of JA and RF. Reactive arthritis was the preliminary diagnosis in 39% and JRA – in 21% of pts at inclusion. Later Juvenile chronic arthritis was the most frequent diagnosis (73-80%). Disease modifying antirheumatic drugs were prescribed early (before 6 months) in 53% of pts. Exacerbations of the disease appeared in 1/3 of pts, more frequently – in pts with polyarthritis. After 12 months functional class 1 remained in 71,4% of pts.Conclusion. Stabilization of pathological process or remission can be achieved in most children with early JA. Pts with polyarthritis sometimes need intensification of treatment (administration of biological agents or change of DMARD. Evaluation of ACCP and MCV can be helpful for diagnosis and prognosis of the disease. Questions of diagnosis, terminology and early verification of diagnosis need further discussion.